Experimental and theoretical study of the color changes in OPP-based printing substrate on the gravure printing - ŞAHİNBAŞKAN, TÜRKÜN (SPRINGER, 2018)
In this study, the color change performances of the prints that are made with gravure printing technique on OPP-based printing substrate used in food packaging are studied experimentally and modeled analytically using artificial neural networks. In this printing technique using solvent ink, small variations in the printing conditions and ink viscosity significantly affect the colors obtained as a result of the printing as the printing surface is not absorbent. In the test print made, samples were taken at certain intervals and color changes were determined with spectrophotometer measurements from test charts. The analytical relation giving the color changes based on the parameters they are linked to was obtained via artificial neural networks. Thus, the color deviations during normal production process shall be determined to ensure that necessary precautions are taken.
Keywords: Gravure printing; OPP-based printing substrate; Artificial neural networks; CIE L*a*b*; ARTIFICIAL NEURAL-NETWORKS